PEMBIAYAAN USAHA KECIL DI INDONESIA - Putri, Risa Haruman; Fauzi, Renie Rahayu; Atmawisastra, R. A. Ginara Utami; Muharam, Sahrial; Redra, Imay Dyna; Alhadi, Izaz (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Small business financing in Indonesia faces various challenges, such as limited access to finance, low financial literacy, and lack of guarantees. Although small businesses contribute significantly to the economy, many SMEs have difficulty obtaining appropriate financing. Various financing alternatives, such as fintech, microcredit, and government programs, are beginning to develop to overcome these obstacles. However, education is still needed related to financial management and increasing access to financing so that SMEs can grow sustainably. This article discusses the current state of small business financing and provides recommendations to improve the effectiveness of the SME financing system in Indonesia.